Enhancing comprehension with e-reading materials / Soo Kum Yoke ... [et al.] - Soo, Kum Yoke; Hasan, Nor Haniza; Jangga, Rohani; Mat Kamal, Siti Nuur-Ila; Mat Nawi, Sofwah (UiTM Cawangan Johor, 2018)
This paper examines the use of e-reading materials for motivating and enhancing reading comprehension among ESL learners. It is part of an ongoing research which experiments with the use of one-sentence short stories in an animated form for cultivating ESL reading habits. The sample comprises 26 respondents majoring in various diploma-level courses in a Malaysian higher learning institution. A reading comprehension test was administered to identify the learners' reading comprehension level according to the Blooms' taxonomy framework. A survey was then conducted to collect data on their perceptions of the e-reading materials. Data from both instruments was analysed using descriptive statistics. The findings of the study indicate that the ESL learners performed significantly well in both lower and higher order thinking skills as a result of using the animated short stories. They also had positive outlook toward the e- reading materials and the use of group discussions for enhancing their comprehension level.